Faktor-Faktor Yang Berhubungan Dengan Penerapan Perilaku Hidup Bersih dan Sehat Pada Rumah Tangga di Wilayah Kerja Puskesmas Tanjung Batu Kab. Ogan Ilir Tahun 2020 - Liliana, Ranti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Implementing clean and healthy living behavior (PHBS) in households is one of the main keys to the success of health development programs in Indonesia. Community awareness and willingness to implement PHBS is expected to be able to maintain and improve their health, prevent the risk of disease and protect themselves from the threat of disease. This research is a quantitative study with a cross-sectional study design with a sample of 44 heads of families. Research data was processed quantitatively using univariate and bivariate analysis methods. The research results showed that the number of respondents based on non-PHBS implementation was 33 (78.5%), while the number of respondents who implemented PHBS was 9 (11.5%). There were respondents with low education (P value 0.003), knowledge (P value 0.000), clean water facilities (P value 0.017), healthy latrines (P value 0.013), income (P value 0.001).